Sustainability Assessment of Rural Water Supply System - Syadzadhiya Qothrunada Zakiyayasin Nisa'; Rizka Novembrianto; Restu Hikmah Ayu Murti; Muhammad Abdus Salam Jawwad (JACEE (Journal of Advanced Civil and Environmental Engineering), 2023)
The commitment to provide clean water and proper sanitation is one of the goals of the Sustainable Development Programs (SDGs). The government of each region needs to strive for clean water for the community. Efforts to fulfill clean water can be realized with the Water Supply System. Water Supply System sustainability indicators need to fulfill three aspects of quality, quantity, and continuity. The aim of this research is to assess the sustainability of the ‘Sugio’ Water Supply System in Lamongan Regency which serves three villages, namely Sugio, Lebakadi, and Sekarbagus. The aspect of water quality, seen from the results of the analysis of the quality of production water, shows that it meets the quality standards as raw water for drinking water. The aspect of water quantity is calculated to meet water needs for the next 20 years. The calculations results show that the daily average debit requirement is 17 L/s and the daily maximum debit is 19 L/s, while the existing debit is 15 L/s. The aspect of water continuity is calculated from the ability to distribute water during an emergency. The calculation results show that the distribution of clean water when there is no source of electrical energy can only be carried out in a maximum of 1 hour 13 minutes 48 seconds. The conclusion obtained is that the sustainability of the ‘Sugio’ Water Supply System from the aspect of water quantity and continuity still needs to be improved.